Improving Emotional Regulation Through Role Awareness Training Among Youth Athletes - Wafiq Alfina Oktafiani; Miftakhul Jannah (Universitas Negeri Surabaya, 2023)
Creating outstanding athletes requires preparation from adolescence so that they can make long-term achievements. However, adolescent athletes are faced with two situations, namely puberty and dual roles that make their responsibilities heavier. This leads to disruption of emotional regulation which is important for adolescent athletes to have. One effort to improve emotional regulation in adolescent athletes is through role awareness training. This study aims to determine the effect of role awareness training on emotional regulation in adolescent athletes. This study uses a quantitative experimental method with a pretest-posttest control group design with the research subject, namely adolescent athletes who live in the training center of the National Potential Young Athletes Center (SLOMPN) as many as 24 people with an age range of 13-15 years old. Emotion regulation was measured using the IERQ4S instrument with a reliability value of .824. The results of this study indicate a difference in the significance value in the experimental group which is 0.01 (0.01 <0.05). While in the control group, it is 0.05 (0.85>0.05). Increased emotion regulation through role awareness training is influenced by intrinsic and extrinsic factors. The results of this study provide advice to future researchers to examine other types of awareness training. Pada proses mencetak atlet yang berprestasi diperlukan persiapan sejak remaja agar mereka dapat mencetak prestasi secara jangka panjang. Namun, atlet remaja dihadapkan pada dua situasi, yaitu pubertas dan peran ganda yang membuat tanggung jawab mereka menjadi lebih berat. Hal ini menimbulkan terganggunya regulasi emosi yang penting untuk dimiliki oleh atlet remaja. Salah satu upaya untuk meningkatkan regulasi emosi pada atlet remaja adalah melalui role awareness training. Penelitian ini bertujuan untuk mengetahui adanya pengaruh role awareness training terhadap regulasi emosi pada atlet remaja. Penelitian ini menggunakan metode kuantitatif eksperimen dengan desain pretest-posttest control group design dengan subjek penelitian yaitu atlet remaja yang menetap di training center Sentra Olahragawan Muda Potensial Nasional (SLOMPN) sebanyak 24 orang dengan rentang usia 13-15 tahun. Regulasi emosi diukur dengan menggunakan instrumen IERQ4S dengan nilai reliabilitas .824. Hasil penelitian ini menunjukkan adanya perbedaan nilai signifikansi pada kelompok ekperimen yaitu 0.01 (0.01<0.05). Sedangkan pada kelompok kontrol yaitu 0.05 (0.85>0.05). Peningkatan regulasi emosi melalui role awareness training dipengaruhi oleh adanya faktor intrinsik dan ekstrinsik. Hasil penelitian ini memberikan saran kepada peneliti selanjutnya untuk mengkaji terkait jenis awareness training yang lainnya.